2006
DOI: 10.1208/aapsj080479
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid mechanisms of pain modulation

Abstract: Cannabinoids are antinociceptive in animal models of acute, tissue injury -, and nerve injury -induced nociception. This review examines the biology of endogenous cannabinoids (endocannabinoids) and behavioral, neurophysiological, and neuroanatomical evidence supporting the notion that cannabinoids play a role in pain modulation. Behavioral pharmacological approaches, in conjunction with the identifi cation and quantifi cation of endocannabinoids through the use of liquid and gas chromatography mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(91 citation statements)
references
References 144 publications
1
86
0
1
Order By: Relevance
“…Because a large body of evidence has clearly demonstrated the antinociceptive action of CB 1 receptor agonists, these results are paradoxical (in that receptor antagonists also have antinociceptive effects; reviewed in refs. [23][24][25][26]. A possible explanation for these paradoxical in vivo effects (by CB 1 agonists and antagonists) could be that endocannabinoids activate distinct signal transduction pathways under different paradigms used to measure pain leading to distinct and opposing effects.…”
Section: Resultsmentioning
confidence: 99%
“…Because a large body of evidence has clearly demonstrated the antinociceptive action of CB 1 receptor agonists, these results are paradoxical (in that receptor antagonists also have antinociceptive effects; reviewed in refs. [23][24][25][26]. A possible explanation for these paradoxical in vivo effects (by CB 1 agonists and antagonists) could be that endocannabinoids activate distinct signal transduction pathways under different paradigms used to measure pain leading to distinct and opposing effects.…”
Section: Resultsmentioning
confidence: 99%
“…As current analgesic treatments for diabetic neuropathy are often considered ineffective and cannabinoids have been pointed out as emerging analgesic therapeutics (Lever and Rice, 2007), there is a growing interest in using these compounds for relieving neuropathic pain (Hohmann and Suplita, 2006), including neuropathic pain associated with diabetes. Previous studies have already demonstrated that local administration of a cannabinoid agonist WIN 55,212-2 is able to reduce mechanical allodynia in diabetic rats, suggesting local administration of cannabinoids as option for treatment of neuropathic pain in diabetic subjects (Ulugol et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Endocannabinoids also possess anti-nociceptive properties, and these have been thoroughly explored in animal models of pain (see references in recent studies [17][18][19]). Many chronic pain states have unknown aetiology and their underlying mechanisms remain unclear.…”
Section: An Overview Of the Cannabinoid Receptor System And Pain Pathmentioning
confidence: 99%